2014
DOI: 10.1007/s00246-014-0908-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Longitudinal Systolic Ventricular Dysfunction and Asynchrony Using Velocity Vector Imaging in Children With a Single Right Ventricle

Abstract: Assessment of ventricular dysfunction and asynchrony is very important in predicting the outcome for children with a single right ventricle. However, the assessment is inaccurate and subjective because of the unusual ventricular shape. This study aimed to evaluate the feasibility and clinical value of velocity vector imaging for assessing longitudinal systolic ventricular dysfunction and intraventricular asynchrony in children with a single right ventricle. The study enrolled 36 children with a single right ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, Kaneko et al [ 17 ] found in a small study (20 children with TCPC, mean age 3.4 years) that global peak longitudinal strain was − 16.6% in children with RV morphology versus − 20.5% in children with LV morphology ( p = 0.01). Studies performed in TCPC patients with only one type of single ventricle morphology report global longitudinal strain values in RV morphology ranging from − 12.0 to − 18.9% [ 7 , 18 21 ] and in LV morphology ranging from − 14.2 to − 18.3% [ 18 , 22 , 23 ]. However, these studies are difficult to compare, since they vary in important factors, including age of study participants, time after completion of the TCPC, type of surgical procedure, type of echocardiographic equipment used, and underlying specific single ventricle morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kaneko et al [ 17 ] found in a small study (20 children with TCPC, mean age 3.4 years) that global peak longitudinal strain was − 16.6% in children with RV morphology versus − 20.5% in children with LV morphology ( p = 0.01). Studies performed in TCPC patients with only one type of single ventricle morphology report global longitudinal strain values in RV morphology ranging from − 12.0 to − 18.9% [ 7 , 18 21 ] and in LV morphology ranging from − 14.2 to − 18.3% [ 18 , 22 , 23 ]. However, these studies are difficult to compare, since they vary in important factors, including age of study participants, time after completion of the TCPC, type of surgical procedure, type of echocardiographic equipment used, and underlying specific single ventricle morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The major strengths of this study are the relatively large number of TCPC patients included and the ability to compare a number of potentially relevant functional parameters, including extensive echocardiographic data (both conventional and innovative parameters such as strain and SR) as well as cMRI data. Other studies using myocardial deformation in single ventricle patients with a TCPC often included rather small numbers of patients [ 7 , 8 , 17 19 , 21 23 , 28 ] which might result in lack of statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…The SRV has the right ventricle anatomy but works as both pulmonic and systemic circulation ventricles; it is usually unable to sustain separate pulmonary and systemic circulations in sequence, nevertheless offering normal ventricular performance. The SRV has impaired systolic and diastolic function compared with that of the respective ventricles in a normal biventricular heart [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recently developed new technique—velocity vector imaging (VVI), based on two‐dimensional images—utilizes ultrasonic speckle tracking to derive directionally unconstrained imaging of myocardial motion, which can be used to estimate regional and global myocardium function. Tissue velocity, S, and SR data had been published for a group of normal fetuses . No studies of fetuses with GDM by VVI have been reported.…”
mentioning
confidence: 99%
“…Tissue velocity, S, and SR data had been published for a group of normal fetuses. 7,8 No studies of fetuses with GDM by VVI have been reported.…”
mentioning
confidence: 99%